Prevalence, Virulence Feature, Antibiotic Resistance and MLST Typing of Bacillus cereus Isolated From Retail Aquatic Products in China - Zhang, Ying; Chen, Mengfei; Yu, Pengfei; Yu, Shubo; Wang, Juan; Guo, Hui; Zhang, Junhui; Zhou, Huan; Chen, Moutong; Zeng, Haiyan; Wu, Shi; Pang, Rui; et al. (Frontiers in Microbiology, 2020)
Bacillus cereus is one of the most important foodborne pathogenic microorganisms, which can lead to gastrointestinal and non-gastrointestinal diseases. However, the potential risk of B. cereus in aquatic products in China has not been comprehensively evaluated yet. In this study, a total of 860 aquatic samples from three types of retail aquatic products were collected from 39 major cities in China from 2011 to 2016. The contamination, distribution of virulence genes, antibiotic resistance and genetic diversity of B. cereus isolates were measured and analyzed. Of all the samples, 219 (25.47%) were positive for B. cereus and 1.83% (4/219) of the samples had contamination levels of more than 1,100 most probable number (MPN)/g. Different isolates had virulence potential, within which 59.6% (164/275) contained all three kinds of enterotoxin genes (nhe, hbl, and cytK-2) and 5.1% (14/275) possessed cereulide encoding gene cesB. The antimicrobial resistance profiles revealed the universal antibiotic resistance to rifampin and most β-lactams, suggesting the necessity to continuously monitor the antibiotic resistance of B. cereus in aquatic products and to control drug use in aquaculture. In sum, our study indicates the potential hazards of B. cereus isolated from aquatic products to customers and may provide a reference for clinical treatment caused by B. cereus.